Preparation method of bamboo fiber reinforced flexible polyurethane foam
By treating bamboo fibers with in-situ regenerated lignin on their surface through low eutectic solvent treatment and enzyme pretreatment, the problem of poor interfacial compatibility between natural fibers and polyurethane matrix in polyurethane foam was solved, the thermal stability, moisture absorption and dissipation properties, and mechanical properties of the foam were improved, and the preparation of high-performance bio-based polyurethane foam was realized.
Patent Information
- Application Number
- CN202510992618.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-10-03
AI Technical Summary
The interface compatibility between natural fibers and the polyurethane matrix in existing polyurethane foams is poor, resulting in uneven stress dispersion and insufficient interface bonding strength, which limits the improvement of the performance of natural fiber-reinforced polyurethane composite foams.
Bamboo fiber was treated with a deep eutectic solvent (DES). Lignin was deposited on the surface of the bamboo fiber as a biocoupling agent, and combined with enzyme pretreatment, bamboo fiber with in situ regenerated lignin on the surface was prepared. The bamboo fiber was then used as a reinforcing component in the preparation of polyurethane foam to improve interfacial compatibility and toughness.
The thermal stability, moisture absorption and dissipation properties and mechanical properties of polyurethane foam have been significantly improved, the preparation of high-performance bio-based polyurethane foam has been realized, the dependence on traditional petroleum-based raw materials has been reduced, and it meets the requirements of green and sustainable development.
Smart Images

Figure CN120737404A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane foam, in particular to a method for preparing bamboo fiber reinforced flexible polyurethane foam. Background Art
[0002] Flexible polyurethane foam (FPUF), also known as polyurethane viscoelastic foam or memory foam, is a special soft polyurethane foam plastic with slow recovery and low rebound properties. FPUF is usually prepared by polyol and isocyanate through a polyaddition reaction, and its polymer chain segment contains repeating urethane structural units. Due to its excellent cushioning and energy absorption properties, FPUF is widely used in bedding and cushioning products such as interior decoration, furniture, car seats, insulation materials, etc. However, the raw materials for the production of FPUF mainly come from non-renewable petrochemical resources. The increasing depletion of petroleum resources and related environmental problems have made traditional petroleum-based polyurethane raw materials increasingly unsustainable. Therefore, the polyurethane industry urgently needs to actively explore and develop composite foams based on natural, environmentally friendly, and renewable materials, as well as reduce dependence on non-renewable petroleum resources, reduce environmental load, and achieve green and sustainable development of polyurethane foam materials.
[0003] Studies have shown that adding natural fibers to polyurethane composite foam can effectively improve its mechanical properties. Natural fibers also give the modified PUF excellent properties such as thermal stability, flexibility, flame retardancy and sound absorption, making it show potential in a wider range of application fields.
[0004] However, the poor compatibility between the natural fiber surface and the hydrophobic polyurethane matrix leads to uneven stress distribution and insufficient interfacial bonding strength, which seriously restricts the further improvement of the performance of natural fiber-reinforced polyurethane composite foams. Therefore, how to effectively improve the interfacial compatibility between natural fibers and the polyurethane matrix is one of the key challenges to fully realizing the performance of natural fiber-reinforced polyurethane foams.
[0005] As a new type of green solvent, deep eutectic solvents (DES) have achieved remarkable results in the separation, extraction, and modification of biomass (especially lignin) in recent years due to their low toxicity, good dissolving power, and environmental friendliness. By using a deep eutectic solvent system, a layer of lignin is deposited on the surface of bamboo fibers as a biocoupling agent. The resulting bamboo fibers can simultaneously achieve enhanced interfacial compatibility and toughened polylactic acid (PLA) matrix. The PLA-based composites have increased their flexural strength, tensile strength, impact strength, and elongation at break by 33.10%, 72.29%, 44.38%, and 40.80%, respectively. Thermal stability and water resistance are also improved. By treating bamboo with DES, lignin can be effectively separated and extracted while protecting the fiber structure of the bamboo, thereby retaining the activity and functionality of the lignin. Recycled lignin can be used as a green alternative in the synthesis of high-performance materials, particularly in the preparation of polyurethane foam. Its inclusion not only improves the foam's mechanical strength, flame retardancy, and biodegradability, but also effectively reduces the use of traditional petroleum-based raw materials, lowering its carbon footprint and environmental impact. Therefore, the recycling of bamboo lignin, particularly through DES solvent recovery and reuse in polyurethane foam, not only contributes to the efficient utilization of bamboo resources but also offers a promising new approach and technological path for the development of environmentally friendly, high-performance polyurethane foam. This process not only promotes the green development of the bamboo industry but also opens up new avenues for the sustainable production of polyurethane foam.
[0006] Enzymes are high-performance catalysts with outstanding specificity for reaction products and can maintain activity even under mild, non-toxic conditions.
[0007] Research using DES solvent to recycle bamboo lignin and apply it to polyurethane foam demonstrates the enormous potential for high-value utilization of bamboo resources and the development of high-performance new polyurethane materials. First, as a green solvent, DES can effectively reduce the environmental pollution risks of traditional chemical solvents, meeting the current demand for green chemistry and clean production. DES solvent treatment enables efficient extraction of bamboo lignin, laying the foundation for subsequent in-situ regeneration and high-value utilization of lignin. Second, using regenerated lignin in polyurethane foam not only replaces some traditional petroleum-based raw materials, reducing the carbon footprint, but also improves the foam's mechanical properties and durability, significantly expanding the application of polyurethane foam.
[0008] In view of this, this application innovatively proposes a method for preparing bamboo fiber reinforced flexible polyurethane foam, prepares bamboo fiber with in-situ regenerated lignin on the surface (ERBF), and uses it as a reinforcing filler to prepare polyurethane soft foam (BPUF), aiming to improve the mechanical properties, comfort and moisture dissipation properties of polyurethane foam. Summary of the Invention
[0009] The object of the present invention is to provide a method for preparing bamboo fiber reinforced flexible polyurethane foam to solve the problems raised in the above background technology.
[0010] To achieve the above object, the present invention provides the following technical solution: a method for preparing bamboo fiber reinforced flexible polyurethane foam, the specific steps of the method for preparing bamboo fiber reinforced flexible polyurethane foam are as follows:
[0011] Step 1. Experimental material selection: Three-year-old moso bamboo was collected from Anji County, Zhejiang Province, China, and naturally air-dried to a moisture content of less than 12%. The bamboo was crushed and passed through a 60-mesh sieve to obtain bamboo fiber, which was set aside. Choline chloride, oxalic acid, xylanase, phosphate buffer solution, ethanol, polyether polyol, isocyanate, diethylaminoethanol, and silicone oil DC5043 were also selected. The experimental instruments selected included a constant temperature and humidity chamber, a mold temperature controller, and an electronic balance.
[0012] Step 2, enzyme pretreatment of bamboo fiber: bamboo fiber was dispersed in 0.05M phosphate buffer solution at a solid-liquid ratio of 5% (w / v), xylanase was added, and the enzyme addition amount was 5% (w / w) of the bamboo fiber mass. The mixture was enzymatically hydrolyzed at 150 rpm in a constant temperature water bath shaker at 40°C for 2 h. After the enzymatic hydrolysis was completed, the mixture was inactivated in a 100°C water bath for 10 min, and then washed with deionized water until the pH of the washing solution was neutral. Finally, it was dried in a 60°C forced air drying oven to constant weight to obtain enzyme pretreated bamboo fiber (EBF);
[0013] Step 3, in situ lignin reorganization of bamboo fiber based on DES: choline chloride (ChCl) and oxalic acid dihydrate were mixed in a molar ratio of 1:1, placed in a beaker, heated in an 80 ° C water bath, and magnetically stirred at a speed of 300 rpm for 1 hour until the mixture was completely melted to form a uniform transparent liquid, that is, choline chloride-oxalic acid dihydrate DES was obtained. The prepared DES was sealed and stored for later use; enzyme pretreated bamboo fiber (EBF) was dispersed in the prepared choline chloride-oxalic acid DES at a solid-liquid ratio of 10% (w / v), and heated in an oil bath at 110 ° C. The mixture was heated and magnetically stirred at 200 rpm for 4 h to fully dissolve the lignin in the bamboo. After the treatment, the mixture was cooled to room temperature, deionized water was added as an anti-solvent, and the mixture was vigorously stirred for 30 min to allow the lignin dissolved in DES to precipitate and deposit on the surface of the bamboo fiber. The mixture was then repeatedly washed with deionized water until the washing liquid was neutral and colorless to remove residual DES and impurities. Finally, the mixture was dried in a 60°C forced air drying oven to constant weight to obtain bamboo fiber with in situ regenerated lignin on the surface (ERBF). Bamboo fiber (RBF) treated directly with DES was used as a control.
[0014] Step 4. Preparation of bamboo fiber reinforced flexible polyurethane foam: polyether polyol, deionized water, silicone oil DC5043 and diethylaminoethanol (DEAE) were weighed according to the formula and mixed evenly in a beaker. ERBF was then added at 1, 2, 3, 4 and 5% of the total polyol mass and stirred at 3500 rpm for 1 min to uniformly disperse the bamboo fiber in the polyol system. MDI was then added and stirred vigorously at 3500 rpm for 10 s to fully mix the components. The mixture was quickly poured into a mold preheated to room temperature and foamed in a mold temperature controller. After foaming was completed, the foam was cured at room temperature for 24 h and then post-cured in a 60°C blast drying oven for 2 h to obtain polyurethane foam. The polyurethane foam without bamboo fiber was used as a blank control (BUF), and the polyurethane foams with in-situ regenerated lignin bamboo fiber (ERBF) added were marked as BPUF.
[0015] Preferably, the choline chloride, oxalic acid, xylanase and ethanol in step 1 are all analytically pure; and the polyether polyol, isocyanate, diethylaminoethanol and silicone oil DC5043 are all industrial grade.
[0016] Preferably, the pH of the phosphate buffer solution in step 2 is 5.0.
[0017] Preferably, the constant temperature and humidity chamber model used in step 1 is Testo 869; the mold temperature controller model is REM-710; and the electronic balance model is TPS2500S.
[0018] Preferably, the size of the mold in step 4 is 20 cm×20 cm×10 cm.
[0019] Preferably, in step three, the deionized water is added in a ratio of 1:10.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1) Enzyme pretreatment and deep eutectic solvent (DES) synergistically achieved in situ lignin reorganization on the bamboo fiber surface. Xylanase pretreatment effectively removed the hemicellulose barrier on the bamboo fiber surface, significantly improving the dissolution efficiency and regeneration selectivity of lignin by the DES solvent. This enabled efficient and targeted regeneration and enrichment of endogenous lignin on the bamboo fiber surface, reshaping the surface chemical composition, micromorphology, and interfacial properties of the bamboo fiber.
[0022] 2) Bio-based polyurethane foam (BPUF) composites prepared with enzymatically regenerated lignin-modified bamboo fiber (ERBF) as a reinforcing component exhibited excellent overall performance. In terms of thermal performance, the thermal stability of BPUF was significantly improved, and the amount of high-temperature residual carbon was significantly increased. In terms of moisture absorption and dissipation, BPUF demonstrated an excellent synergistic effect, with a moisture dissipation rate of up to 97.04%, effectively improving the breathability and comfort of the foam. In terms of mechanical properties, the compression, tensile, and tear strength of BPUF were all comprehensively enhanced, with the tear strength increased by more than 50%.
[0023] 3) This process is environmentally friendly, using raw materials derived from renewable biomass. The resulting polyurethane foam product exhibits excellent performance, fully embodying the principles of clean production and sustainable development. This technology provides new ideas and methods for the development and application of high-performance bio-based polyurethane foam materials, and is expected to promote the transformation and upgrading of the polyurethane foam industry towards a green and sustainable direction. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the preparation of BPUF from bamboo fiber based on enzymatic treatment and DES mediation;
[0025] Figure 2 This is the tensile specimen diagram;
[0026] Figure 3 This is the tearing specimen diagram;
[0027] Figure 4 is the compression specimen diagram;
[0028] Figure 5 The morphological structure and structural feature diagram of BF, RBF and ERBF;
[0029] Figure 6 is the microscopic morphology of the bamboo fiber surface;
[0030] Figure 7 The physical and chemical parameters and foam performance analysis diagram of PUF and BPUF;
[0031] Figure 8 Thermal stability analysis diagram of PUF and BPUF;
[0032] Figure 9 The water absorption and moisture dissipation performance analysis diagram of PUF and BPUF;
[0033] Figure 10 Fourier infrared images of PUF and BPUF;
[0034] Figure 11 Compression performance analysis diagram of PUF and BPUF;
[0035] Figure 12Mechanical properties diagram of PUF and BPUF;
[0036] Figure 13 The tensile and tearing properties analysis diagram of PUF and BPUF;
[0037] Figure 14 SEM images of the pore structure of PUF and BPUF and the pore diameter distribution diagram.
[0038] In the picture:
[0039] Figure 5 Middle: (a) Schematic diagram of bamboo fiber morphology before and after modification, (b) FTIR spectrum (c) XPS spectrum, (d) XRD spectrum;
[0040] Figure 6 In: (ac)BF, (df)RBF and (gi)ERBF;
[0041] Figure 7 Middle: (a) Viscosity images of PUF and BPUF, (bc) Creaming time, extension time, and gel time of PUF and BPUF;
[0042] Figure 8 Middle: (a) TG images of PUF and BPUF, (b) DTG images of PUF and BPUF;
[0043] Figure 9 Middle: (a) Water absorption rate images of PUF and BPUF, (b) Moisture dissipation rate images of PUF and BPUF;
[0044] Figure 11 Middle: (a) stress-strain curves, (bg) stress and energy dissipation of PUF and BPUF;
[0045] Figure 12 Middle: (a) indentation hardness, (b) compression deflection coefficient and hysteresis loss rate of PUF and BPUF;
[0046] Figure 13 Middle: (a) Tensile strength of PUF and BPUF, (b) Tear strength of PUF and BPUF, (c) Reinforcement mechanism diagram of PUF and BPUF. DETAILED DESCRIPTION
[0047] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0048] Example:
[0049] See also Figure 1-14 , the present invention provides a technical solution:
[0050] A method for preparing bamboo fiber reinforced flexible polyurethane foam. The specific steps of the method for preparing bamboo fiber reinforced flexible polyurethane foam are as follows:
[0051] Step 1. Experimental material selection: Three-year-old moso bamboo was collected from Anji County, Zhejiang Province, China, and naturally air-dried to a moisture content of less than 12%. The bamboo was crushed and passed through a 60-mesh sieve to obtain bamboo fiber, which was set aside. Choline chloride, oxalic acid, xylanase, phosphate buffer solution, ethanol, polyether polyol, isocyanate, diethylaminoethanol, and silicone oil DC5043 were also selected. The experimental instruments selected included a constant temperature and humidity chamber, a mold temperature controller, and an electronic balance.
[0052] Step 2, enzyme pretreatment of bamboo fiber: bamboo fiber was dispersed in 0.05M phosphate buffer solution at a solid-liquid ratio of 5% (w / v), xylanase was added, and the enzyme addition amount was 5% (w / w) of the bamboo fiber mass. The mixture was enzymatically hydrolyzed at 150 rpm in a constant temperature water bath shaker at 40°C for 2 h. After the enzymatic hydrolysis was completed, the mixture was inactivated in a 100°C water bath for 10 min, and then washed with deionized water until the pH of the washing solution was neutral. Finally, it was dried in a 60°C forced air drying oven to constant weight to obtain enzyme pretreated bamboo fiber (EBF);
[0053] Step 3, in situ lignin reorganization of bamboo fiber based on DES: choline chloride (ChCl) and oxalic acid dihydrate were mixed in a molar ratio of 1:1, placed in a beaker, heated in an 80 ° C water bath, and magnetically stirred at a speed of 300 rpm for 1 hour until the mixture was completely melted to form a uniform transparent liquid, that is, choline chloride-oxalic acid dihydrate DES was obtained. The prepared DES was sealed and stored for later use; enzyme pretreated bamboo fiber (EBF) was dispersed in the prepared choline chloride-oxalic acid DES at a solid-liquid ratio of 10% (w / v), and heated in an oil bath at 110 ° C. The mixture was heated and magnetically stirred at 200 rpm for 4 h to fully dissolve the lignin in the bamboo. After the treatment, the mixture was cooled to room temperature, deionized water was added as an anti-solvent, and the mixture was vigorously stirred for 30 min to allow the lignin dissolved in DES to precipitate and deposit on the surface of the bamboo fiber. The mixture was then repeatedly washed with deionized water until the washing liquid was neutral and colorless to remove residual DES and impurities. Finally, the mixture was dried in a 60°C forced air drying oven to constant weight to obtain bamboo fiber with in situ regenerated lignin on the surface (ERBF). Bamboo fiber (RBF) treated directly with DES was used as a control.
[0054] Step 4. Preparation of bamboo fiber reinforced flexible polyurethane foam: polyether polyol, deionized water, silicone oil DC5043 and diethylaminoethanol (DEAE) were weighed according to the formula and mixed evenly in a beaker. ERBF was then added at 1, 2, 3, 4 and 5% of the total polyol mass and stirred at 3500 rpm for 1 min to uniformly disperse the bamboo fiber in the polyol system. MDI was then added and stirred vigorously at 3500 rpm for 10 s to fully mix the components. The mixture was quickly poured into a mold preheated to room temperature and foamed in a mold temperature controller. After foaming was completed, the foam was cured at room temperature for 24 h and then post-cured in a 60°C blast drying oven for 2 h to obtain polyurethane foam. The polyurethane foam without bamboo fiber was used as a blank control (BUF), and the polyurethane foams with in-situ regenerated lignin bamboo fiber (ERBF) added were marked as BPUF.
[0055] like Figure 1 As shown, the present application adopts an efficient biological process based on enzyme chemistry, without the need for artificial activators. Xylanase selectively enzymatically degrades the hemicellulose in the wood and retains the cellulose and lignin therein, thereby maintaining the complete morphology of the bamboo fiber. The bamboo material pretreated with the enzyme is then extracted with DES and then regenerated using an anti-solvent (water). The bamboo fiber (ERBF) that has been pretreated with enzymatic hydrolysis and regenerated with hydrophobic lignin has good compatibility with polyurethane foam, achieving a synergistic improvement in the mechanical properties, comfort and moisture dissipation properties of BPUF. This method is simple, environmentally friendly and efficient, and this strategy is also expected to be promoted and applied to the modification of polyurethane foam reinforced with various biomass fillers such as wood powder, corn straw, and cotton stalks.
[0056] The specifications of the choline chloride, oxalic acid, xylanase and ethanol used in the step 1 are all analytical grade; the specifications of the polyether polyol, isocyanate, diethylaminoethanol and silicone oil DC5043 used are all industrial grade.
[0057] The pH of the phosphate buffer solution in step 2 is 5.0.
[0058] The constant temperature and humidity chamber model used in step 1 is Testo 869; the mold temperature controller model is REM-710; and the electronic balance model is TPS2500S.
[0059] The size of the mold in step 4 is 20 cm×20 cm×10 cm.
[0060] In the step 3, the deionized water is added in a ratio of 1:10.
[0061] Water absorption and moisture dissipation performance test:
[0062] Water absorption and water dissipation test of foam was conducted according to ISO 22649:2016. The sample size was 5×5×5cm 3 , the sample weight is recorded as m0, then the sample is soaked in distilled water for 6 hours, taken out and the water droplets remaining on the surface are absorbed by filter paper, and the sample weight is recorded as m w Then, place the sample in a constant temperature and humidity chamber, measure its weight at regular intervals, and record it as m R , the water absorption of foam (W A ) and water dissipation capacity (W D ) are calculated using Formulas 3-1 and 3-2 respectively:
[0063]
[0064] Mechanical properties test:
[0065] The mechanical properties of PUF and BPUF were analyzed using tensile properties, tear resistance, and support properties (compression deflection coefficient, hysteresis loss rate, and indentation hardness). The tensile properties test was conducted according to ISO 1798-2008. Type 1A-sized dumbbell specimens were used for the test. Five dumbbell-shaped specimens were tested at a rate of 500 mm / min to obtain the tensile strength of the samples.
[0066] The tearing performance test adopts ISO 8067-2008 standard, the sample size is 25×25×125mm, and the sample is tested at a rate of 500mm / min;
[0067] According to ISO 2439:2008(E), foam (20×20×10cm 3 ) are measured for the compression deflection coefficient, hysteresis loss rate and indentation hardness characteristics. The movement speed of the testing machine's indenter is 100 mm / min. The specimen is compressed to (25±1)%, (40±1)%, and (65±1)% of the total thickness, and the load is maintained for (30±1) s respectively. The pressure is recorded to characterize its indentation hardness characteristics HB (25% / 30s), HB (40% / 30s), and HB (65% / 30s). In addition, the compression deflection coefficient (Sf) and hysteresis loss rate (Af) are measured by compressing the specimen to (75±1)% of the total thickness and then unloading. The compression deflection coefficient, hysteresis loss rate and indentation hardness characteristics are carried out in accordance with ISO 2439:2008(E). Compression deflection coefficient (S f ) and hysteresis loss rate (A f ) and are calculated using Formulas 3-3 and 3-4 respectively;
[0068]
[0069] Among them: F65 F is the force when the compression reaches 65%. 25 It is the force when the compression reaches 25%.
[0070]
[0071] Where: A1 is the area between the loading curve and the unloading curve, A2 is the area between the loading curve and the x-axis;
[0072]
[0073] Surface characteristics and crystallinity analysis of bamboo:
[0074] Figure 5 The morphology, structure and composition characteristics of BF, RBF and ERBF were shown. Fourier transform infrared spectroscopy (FTIR) analysis provided direct evidence for a deeper understanding of the modification effect of enzyme pretreatment on the chemical composition of bamboo fiber. The spectrum of bamboo fiber (BF) without any treatment is at 1730 cm 1 The characteristic peak is clearly attributed to the stretching vibration of the ester group (C=O) in hemicellulose, which confirms that the original bamboo fiber is rich in hemicellulose components. However, after the pretreatment of xylanase, the peak at 1730 cm in the ERBF spectrum is 1 The characteristic ester peak at the position almost completely disappeared, indicating that xylanase effectively degraded and removed the hemicellulose components in bamboo fiber, laying an important structural foundation for the subsequent deep eutectic solvent (DES)-mediated lignin regeneration process.
[0075] More importantly, the FTIR spectrum of ERBF is at 1600 cm 1 、1270cm 1 and 1200cm 1 In the equal wave number region, the absorption peak intensity representing the characteristic functional groups of lignin is significantly enhanced. Specifically, at 1600 cm 1 The strong absorption peak at 1270 cm corresponds to the C=C stretching vibration of the aromatic ring skeleton of lignin, while the 1 and 1200cm 1 The nearby absorption peaks are attributed to the stretching vibrations of CO and CC in the guaiacyl units of lignin. The significant enhancement of these lignin characteristic peaks, coupled with the disappearance of the characteristic peaks of hemicellulose, confirms that through the synergistic effect of enzyme pretreatment and DES, endogenous lignin successfully migrated from the interior of the bamboo cell wall and accumulated on the surface of the bamboo fiber, forming a modified bamboo fiber with rich surface lignin.
[0076] X-ray photoelectron spectroscopy further validated the FTIR spectroscopy results from the perspective of elemental composition and chemical state. The C1s XPS spectrum of the bamboo fiber (BF) exhibited distinct characteristic peaks at 284.8 eV, 286.56 eV, 288.13 eV, and 289.14 eV. These peaks correspond to carbon atoms with different chemical bond types, including CC / CH (carbon chain and carbon-hydrogen bond), CO, OCO / C=O (glycosidic bond / carbonyl group), and OC=O (carboxyl group), in the main bamboo components of cellulose, hemicellulose, and lignin. The slight increase in the CC / CH and OCO / C=O peak intensities in the RBF spectrum suggests that DES treatment may, to some extent, promote the migration of endogenous lignin to the bamboo fiber surface. The significant decrease in the OC=O peak intensity and the further significant increase in the CC / CH and OCO / C=O peak intensities in the ERBF spectrum strongly confirm that the synergistic effect of enzyme pretreatment and DES significantly enhances the regeneration and enrichment of lignin on the bamboo fiber surface and further reduces the hemicellulose content. The XPS results are highly consistent with the FTIR spectral analysis results, providing strong chemical evidence for the efficient regeneration of lignin on the surface of bamboo fiber by enzyme pretreatment combined with DES technology from the perspective of elemental composition and chemical state.
[0077] X-ray diffraction analysis showed that BF, RBF, and ERBF all exhibited typical cellulose type I crystal structure characteristics, with characteristic diffraction peaks of cellulose observed at 2θ = 15.53°, 16.32°, 22.56°, and 34.78°. As shown in Table 3, the cellulose crystallinity index was calculated, and it was found that the crystallinity of BF, RBF, and ERBF was 33.67%, 40.86%, and 42.05%, respectively. The increase in crystallinity of RBF and ERBF compared to BF indicates that DES treatment can effectively remove the amorphous components (mainly hemicellulose and some amorphous cellulose) in bamboo fiber, thereby relatively improving the crystallinity of cellulose. The further slight increase of 1.19% in crystallinity of ERBF compared to RBF may be attributed to the effective removal of hemicellulose in bamboo fiber by xylanase pretreatment, which further increases the relative content of cellulose and the crystallinity. The XRD analysis results corroborated the conclusions of FTIR and XPS analysis, further confirming the effectiveness of enzyme pretreatment combined with DES technology in regulating the chemical composition and structure of bamboo fiber.
[0078] Microscopic morphology study of bamboo fiber surface morphology:
[0079] In order to more intuitively explore the effect of xylanase pretreatment on the regeneration of lignin on the surface of bamboo fiber, the surface morphology of BF, RBF and ERBF was studied using scanning electron microscopy (SEM). Figure 6As shown in the figure, the surface of untreated BF is relatively smooth and flat, exhibiting a typical natural bamboo fiber morphology. However, the surface morphology of RBF modified with DES undergoes some changes, with increased roughness and a small number of dot-like and flake-like particles observed adhering to the surface. These particles likely form during the DES treatment, when partially dissolved lignin redeposits on the fiber surface. Compared to BF and RBF, the surface morphology of ERBF undergoes even more significant changes, with a significantly increased surface roughness. A large number of granular materials can be clearly observed covering the fiber surface. These particles interconnect, forming a distinct striped attachment layer, giving the ERBF surface a distinct grooved and layered structure. The attachments on the fiber surface show a clear trend of increasing thickness. Combined with the aforementioned FTIR and XPS analysis results, it is inferred that the thick layers of attachments covering the ERBF surface are primarily recycled lignin. This confirms that xylanase pretreatment significantly enhances the efficiency of DES solvent-induced lignin regeneration in bamboo, allowing more lignin to be efficiently deposited on the bamboo fiber surface. The large amount of regenerated lignin deposited on the fiber surface not only significantly changes the surface morphology of the bamboo fiber, but also inevitably affects the surface physical and chemical properties of the bamboo fiber, laying an important foundation for the subsequent application of bamboo fiber in polyurethane foam. In addition, the improvement of the surface roughness of ERBF will help enhance the mechanical interlocking effect between it and the polyurethane matrix, thereby improving the interfacial bonding strength of the composite material.
[0080] Analysis of PUF and BPUF physical and chemical parameters and foam properties:
[0081] Table 4 Reaction system parameters
[0082]
[0083]
[0084] Table 5 Apparent density and porosity of PUF and BPUF
[0085] Table 4 and Figure 7 Reaction parameters such as viscosity, cream time, elongation time, and gel time of polyol mixtures without ERBF (PUF) and with varying ERBF contents (BPUF-1 to BPUF-5) are summarized. Cream time marks the onset of bubble nucleation in the foaming system, elongation time reflects the rate at which the foam expands to its maximum volume, and gel time characterizes the transition from liquid to solid. These reaction parameters are closely related to the ultimate properties of polyurethane foam, such as its microstructure, density, and mechanical properties.
[0086] As shown in Table 4, the viscosity of the PUF polyol system without ERBF was 574.67 mPa·s. As the amount of ERBF added increased, the viscosity of the polyol system showed a gradual upward trend. When the ERBF addition increased from 1% to 5%, the viscosity of the mixture system increased significantly from 738.67 mPa·s to 917.00 mPa·s. This is mainly due to the high specific surface area and surface energy of bamboo fiber particles. Their dispersion in the polyol system increases the internal friction resistance of the system, thereby increasing the viscosity of the mixture system. In addition, the addition of high concentrations of ERBF may also cause a certain degree of agglomeration of fiber particles in the system, further exacerbating the increase in system viscosity.
[0087] Cream time generally refers to the time from the start of the polymer reaction, from the mixing of the raw materials to the moment the material surface appears milky white (i.e., the beginning of the foam structure). During this period, the polyurethane system undergoes chemical reactions, gradually transforming the liquid raw materials into a solid foam. Extension time refers to the time from the start of the cream time to the point when the foam volume stabilizes or the material is further processed and molded. During this period, the polymer continues to expand and form the foam structure, typically involving gas generation and foam expansion. Gel time refers to the time it takes for a polyurethane or other polymer system to transform from a liquid reaction mixture into a semi-solid gel. During this stage, the chemical reaction progresses to the formation of a three-dimensional network structure, the polymer chains crosslink, and the material gradually transitions from a fluid state to a solid state. Consistent with the viscosity trend, the cream time, extension time, and gel time of the polyol system all increase with increasing ERBF addition. This extended reaction time is primarily due to the fact that the increased viscosity of the system hinders the foaming reaction, reduces the growth and expansion rate of bubbles, and delays the crosslinking and curing of the polyurethane molecular chains.
[0088] Figure 7Table c and Table 5 show the apparent density and porosity of PUF and BPUF. Compared with PUF, the porosity of BPUF first increases and then decreases with increasing ERBF addition, while the apparent density of polyurethane foam first decreases and then increases. The phenomenon of the porosity of BPUF first increasing and then decreasing may be related to the dual role of ERBF in the polyurethane foaming system. At low addition levels (such as BPUF-1 and BPUF-2), ERBF primarily acts as a heterogeneous nucleating agent, promoting uniform bubble nucleation and increasing the number of bubbles, thereby increasing the porosity of the foam and reducing the density. In addition, bamboo fiber itself has a low density and hollow tubular structure, and its addition also helps to reduce the overall density of the foam. However, at high addition levels (such as BPUF-3 to BPUF-5), the high viscosity effect of ERBF begins to dominate. High viscosity is not conducive to the growth and expansion of bubbles, resulting in a decrease in porosity and an increase in density. Therefore, the changes in porosity and density of BPUF are the result of the combined effects of ERBF nucleation and high viscosity;
[0089] Thermal stability analysis of PUF and BPUF:
[0090] Figure 8 Thermogravimetric (TG) and differential thermogravimetric (DTG) curves of PUF and BPUF were presented to investigate the effect of ERBF on the thermal stability and thermal degradation behavior of polyurethane foam. The TG curves reveal that both PUF and BPUF exhibit a similar two-step thermal degradation behavior, consistent with the typical thermal degradation mechanism of polyurethane foam. The first thermal degradation stage (approximately 200-350°C) is primarily attributed to the cleavage of urethane bonds and decomposition of urea bonds in the polyurethane hard segment. The second thermal degradation stage (approximately 350-500°C) corresponds primarily to the degradation of the polyether polyol soft segment and the cleavage of carbon chains. The PUF exhibited a carbon residue of 7.75%. Similar to PUF, the thermal degradation process of BPUF is divided into two main stages. When the ERBF addition level was 3%, the final carbon residue of BPUF reached 10.22%. This increase in carbon residue indicates that the addition of ERBF effectively improves the thermal stability of polyurethane foam and may also enhance its flame retardant properties. This is mainly because the lignin in bamboo fiber has high thermal stability and carbonization tendency, which can form more carbon layers during the thermal degradation process, thereby effectively hindering the release of heat and combustible gases and increasing the amount of residual carbon.
[0091] Analysis of water absorption and moisture dissipation performance of PUF and BPUF:
[0092] Table 6 Water absorption of PUF and BPUF
[0093]
[0094]
[0095] Figure 9 Table 6 and Table 7 respectively show the water absorption and moisture dissipation of BPUF at different ERBF addition amounts. Water absorption and moisture dissipation performance are important indicators for evaluating the comfort and service life of polyurethane foam, especially for applications such as mattresses and pillows that have long-term contact with human skin. Figure 6 As shown in Figure a, the water absorption of BPUF shows a trend of first increasing and then decreasing with increasing ERBF addition, reaching a maximum at 2% ERBF addition (BPUF-2, water absorption approximately 2901%), and then gradually decreasing to 2093% for BPUF-5. The variation in BPUF water absorption may be related to its pore structure and fiber addition. At low ERBF addition levels, the nucleation effect of ERBF leads to an increase in foam porosity. More pores provide more water storage space, thereby improving water absorption. Furthermore, bamboo fiber has a certain degree of water absorption, and its addition also helps to improve the water absorption capacity of the foam. However, with further increases in ERBF addition, the pore size of the BPUF gradually increases. Excessively large pores are not conducive to water retention, resulting in a decrease in water absorption. Furthermore, the lignin enriched on the ERBF surface contains a large number of hydrophobic groups. The addition of a high ERBF content increases the overall hydrophobicity of the foam, which may also lead to a decrease in water absorption. Therefore, the water absorption performance of BPUF is a complex result of the interaction between pore structure and surface chemical composition.
[0096] In contrast to the trend of changes in water absorption performance, the moisture dissipation rate of BPUF shows a gradual upward trend with the increase in the amount of ERBF added. The moisture dissipation rate of PUF without ERBF added was only 81.76% after 120 hours, while the moisture dissipation rate of BPUF-5 with 5% ERBF added was as high as 97.04% after 120 hours, an increase of 15.28%. The improvement in the moisture dissipation rate of BPUF is mainly attributed to the following aspects: First, the addition of ERBF increases the open porosity of the foam. More open pores provide more channels for the loss of water molecules, which is conducive to the rapid diffusion and evaporation of water molecules. Secondly, the hydrophobic lignin enriched on the surface of ERBF and the hollow tubular structure of bamboo fiber also contribute to the loss of water molecules. The excellent moisture dissipation performance gives BPUF better comfort, so that when it is used as a filling material for mattresses, pillows, etc., it can effectively reduce the accumulation of moisture and heat, improve the comfort of use and the service life of the product, and ultimately reduce the waste of polyurethane foam, which is in line with the concept of green and sustainable development.
[0097] FTIR spectrum analysis of polyurethane foam of PUF and BPUF:
[0098] Figure 10The FTIR spectra of PUF and BPUF are shown. The FTIR spectra of PUF and BPUF are similar, both showing the typical characteristic absorption peaks of polyurethane foam. 1 and 2850-2960cm 1 The absorption peak in the range is attributed to the stretching vibration of the C-H bond, 1715 cm 1 The absorption peak at 1227 cm corresponds to the stretching vibration of the C=O bond in the ester group (-COO-) or amide group (-CONH-) in the polyurethane foam. 1 and 1097cm 1 The absorption peaks at 813 cm are attributed to the stretching vibration of the C-O-C bond and the C-O bond. 1 The absorption peak at is likely related to the bending vibration of the C-H bond in aromatic compounds. The characteristic absorption peak of ERBF is absent from the BPUF spectrum. This may be due to the low amount of ERBF added to the polyurethane foam, resulting in a relatively weak characteristic peak intensity that is masked by the strong absorption peak of the polyurethane foam. Nevertheless, the FTIR spectrum results still confirm the successful preparation of the polyurethane foam.
[0099] Compression performance analysis of PUF and BPUF:
[0100] Table 7 Densification strain of PUF and BPUF
[0101]
[0102] Figure 11 Figure a shows the quasi-static uniaxial compression stress-strain curves for PUF and BPUF. As can be seen from the figure, the compression process of both PUF and BPUF can be divided into three typical stages: the elastic stage, the plateau stage, and the densification stage. In the elastic stage, the foam undergoes elastic deformation under the action of the compressive force, and the stress increases linearly with the strain. The foam structure does not change significantly, and the volume can basically recover. After entering the plateau stage, the foam yields, the stress increases slowly, the bubbles are gradually compressed, and the foam structure is irreversibly destroyed. As the strain increases further, the densification stage is entered, the foam structure is completely compacted, and the stress increases sharply.
[0103] In order to quantitatively analyze the effect of ERBF on the densification behavior of polyurethane foam, the energy absorption efficiency method was used to calculate the densification strain of PUF and BPUF ( Figure 11 bg). The energy absorption efficiency method is based on the energy absorption characteristics of foam during compression, and the strain corresponding to the maximum energy absorption efficiency is defined as the densification strain. Figure 11b and Table 7 show that the densification strain of PUF is 0.644. Compared with PUF, the densification strain of BPUF is lower, and with the increase of ERBF addition, the densification strain shows a gradually decreasing trend. When the ERBF addition amount is 5%, the densification strain of BPUF-5 is reduced to 0.602. The reduction in densification strain indicates that the addition of ERBF can improve the structural stability of polyurethane foam, making it less prone to structural collapse and densification during compression. This may be attributed to the effective interfacial interaction formed between ERBF and the polyurethane matrix, which improves the overall structural strength and resistance to compression deformation of the foam. For support and load-bearing applications, a smaller densification strain is generally more advantageous, which means that the material can maintain better shape stability and load-bearing capacity after being subjected to stress;
[0104] Table 8 Hysteresis loss rate, compression deflection coefficient and indentation hardness
[0105]
[0106]
[0107] Indentation hardness is an important indicator for evaluating the comfort and support performance of soft foam. Figure 12 Table 8 shows the indentation hardness (HB25, HB40, and HB65) of PUF and BPUF at three different compressive strains: 25%, 40%, and 65%. As shown in the figure, the indentation hardness of PUF at 25%, 40%, and 65% strains is 10.38N, 13.83N, and 23.39N, respectively. Compared with PUF, the indentation hardness of BPUF is improved to varying degrees, and the indentation hardness shows a gradual increase with increasing ERBF addition. This indicates that the addition of ERBF can effectively improve the hardness and support properties of polyurethane foam. The increase in indentation hardness can also be attributed to the enhanced interfacial interaction between ERBF and the polyurethane matrix, making the foam structure more compact and strong.
[0108] Compression deformation coefficient (S f ) and hysteresis loss rate (A f ) is an important parameter for evaluating the compression recovery performance and energy absorption performance of polyurethane foam. f ) is defined as 25% indentation hardness (F 25 ) and 65% indentation hardness (F 65 ) ratio (S f =F 25 / F 65 ), S f The smaller the value, the better the compression recovery performance of the foam. f ) reflects the energy loss of the foam during the compression cycle, Af The smaller the value, the better the energy recovery performance of the foam. Figure 12 As shown, the compression deformation coefficient of PUF is 2.25, and the hysteresis loss rate is 31.66%. The compression resistance coefficient of BPUF first increases and then decreases with the addition of ERBF. When the addition amount is 4%, the compression deformation coefficient of BPUF-4 reaches 2.75, an increase of 0.5 compared to the blank sample (2.25). The higher the compression deformation coefficient, the softer the surface and the better the bottom support performance. The hysteresis loss rate of foam is a key parameter for measuring the energy loss of foam materials during compression. It refers to the energy loss caused by the material during rebound. With the increase of ERBF content, the hysteresis loss rate of BPUF gradually decreases. When the ERBF addition reaches 5%, the hysteresis loss rate of BPUF-5 reaches 32.49%. This may be related to the heterogeneous nucleation effect of ERBF and the interfacial interaction formed between ERBF and the polyurethane matrix, which makes the foam structure more uniform and stable, and the elastic recovery performance is better. However, when the ERBF addition amount is too high, the uniformity of the foam structure decreases and defects increase due to the high viscosity effect and fiber agglomeration, resulting in a decrease in compression recovery performance and energy absorption performance.
[0109] Analysis of tensile and tear properties of PUF and BPUF:
[0110] Table 9 Tensile and tear properties of PUF and BPUF
[0111]
[0112]
[0113] Figure 13 The tensile strength of PUF and BPUF is summarized in (a) and Table 9. The tensile strength and elongation at break of PUF are 0.41 N mm -1 . Compared with PUF, the tensile strength of BPUF first increases and then decreases with the addition of ERBF. When the ERBF addition amount is 4%, the tensile strength and elongation at break of BPUF-4 both reach their maximum values, which are 22.47KPa respectively, which are 40.01% higher than those of PUF. The increase in tensile strength and elongation at break indicates that the addition of an appropriate amount of ERBF can effectively improve the tensile properties of polyurethane foam. This is mainly due to the formation of an effective stress transfer interface between ERBF and the polyurethane matrix, which improves the overall bearing capacity and tensile deformation resistance of the foam. In addition, bamboo fiber itself has a high tensile strength, and its addition also helps to improve the tensile properties of the foam. However, when the amount of ERBF added is too high, due to problems such as fiber agglomeration and uneven dispersion, the internal defects of the foam increase, the stress concentration phenomenon intensifies, and the tensile properties decrease.
[0114] Tear strength is an important indicator for evaluating the tear resistance of polyurethane foam, which directly affects the service life and reliability of the foam. Figure 13 (b) shows the tear strength test results of PUF and BPUF. The tear strength of PUF is 0.41N mm -1 Compared with PUF, the tear strength of BPUF is significantly improved, and with the increase of ERBF addition, the tear strength shows a trend of increasing first and then decreasing. When the ERBF addition is too large, the tear strength decreases at the same time as the tensile strength. When the ERBF addition is 4%, the tear strength of BPUF-4 is as high as 0.65mm. -1 , which is 58.54% higher than that of PUF. The significant improvement in tear strength shows that the addition of ERBF can greatly improve the tear resistance of polyurethane foam. This is mainly due to the high toughness and tear resistance of bamboo fiber, and its addition can effectively disperse stress and prevent crack propagation. In addition, the interfacial interaction formed between ERBF and the polyurethane matrix also helps to improve the tear resistance of the foam. The excellent tear resistance gives BPUF a longer service life and higher reliability, making it more advantageous in applications with high durability requirements. Figure 13 (c) A possible mechanism is proposed: lignin forms a bonding interaction with the polar groups of cellulose, and the non-polar groups of the polyurethane foam (alkyl groups and aromatic groups, etc.) may interact with non-polar groups such as -OCH3 and benzene rings in lignin to form bonds. Furthermore, ERBF, as a high-strength fiber-reinforced filler, can withstand and transmit applied loads, transferring stress from the polyurethane matrix to itself, thereby improving the overall load-bearing capacity of the foam.
[0115] Analysis of PUF and BPUF cell structure:
[0116] like Figure 11As shown, SEM images of polyurethane foam were obtained, along with histograms of the cell diameter distribution of BPUF and PUF with varying ERBF content. As shown in Figures af, both PUF and BPUF exhibit open-cell structures. With increasing ERBF content, the number of open cells in BPUF increases. This increased number of open cells generally indicates more voids within the foam, leading to lower foam density and better pore connectivity, thus improving the foam's breathability. This provides better air circulation, reduces the feeling of stuffiness caused by moisture accumulation, and enhances user comfort. Image J mathematical measurements of the images yielded the cell frequency distribution histograms shown in Figures a1-f1. The pore diameter of the PUF is 574.3 μm. With increasing ERBF content, the pore diameter of the BPUF increases from 604.05 μm to 679.32 μm. Increased pore diameter generally indicates enhanced foam breathability, which contributes to improved comfort. This is particularly true in products such as mattresses and cushions, where increased breathability can reduce heat and moisture accumulation, enhancing user comfort. A larger cell diameter may cause the foam to absorb moisture more easily, and the foam may feel softer or lighter, making it suitable for use in mattresses or pillows that require a soft or comfortable touch.
[0117] This application discusses the application of enzyme pretreatment and DES-mediated lignin reorganization technology in the preparation of high-performance bio-based polyurethane foam materials, as well as the effect of enzyme pretreatment on material properties. Make full use of renewable bamboo resources and produce environmentally friendly bio-based polyurethane foam materials through a simple and environmentally friendly method. The proposed method can reduce environmental pollution caused by improper treatment of waste bamboo, achieve efficient recycling of waste bamboo resources, and solve the problems of insufficient performance of current plant-based biomass polyurethane foam materials. The results of this application show that bamboo fiber and its enzymatically regenerated lignin-modified derivatives show great potential in the development of biomass polyurethane foam materials. Enzyme pretreatment and DES-mediated lignin regeneration technology can provide a simple, efficient and environmentally friendly solution for the development of biomass polyurethane foam materials.
[0118] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the appended claims rather than the above description. Therefore, it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any figure signs in the claims should not be regarded as limiting the claims involved.
[0119] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing bamboo fiber reinforced flexible polyurethane foam, characterized in that: The specific steps of the preparation method of bamboo fiber reinforced flexible polyurethane foam are as follows: Step 1. Experimental material selection: Three-year-old moso bamboo was collected from Anji County, Zhejiang Province, China, and naturally air-dried to a moisture content of less than 12%. The bamboo was crushed and passed through a 60-mesh sieve to obtain bamboo fiber, which was set aside. Choline chloride, oxalic acid, xylanase, phosphate buffer solution, ethanol, polyether polyol, isocyanate, diethylaminoethanol, and silicone oil DC5043 were selected. The experimental instruments selected included a thermogravimetric analyzer, a constant temperature and humidity chamber, a mold temperature controller, and an electronic balance. Step 2, enzyme pretreatment of bamboo fiber: bamboo fiber was dispersed in 0.05M phosphate buffer solution at a solid-liquid ratio of 5% (w / v), xylanase was added, and the enzyme addition amount was 5% (w / w) of the bamboo fiber mass. The mixture was enzymatically hydrolyzed at 150 rpm in a constant temperature water bath shaker at 40°C for 2 h. After the enzymatic hydrolysis was completed, the mixture was inactivated in a 100°C water bath for 10 min, and then washed with deionized water until the pH of the washing solution was neutral. Finally, it was dried in a 60°C forced air drying oven to constant weight to obtain enzyme pretreated bamboo fiber (EBF); Step 3: In-situ lignin reorganization of bamboo fiber based on DES: Choline chloride (ChCl) and oxalic acid dihydrate were mixed in a molar ratio of 1:1, placed in a beaker, heated in an 80°C water bath, and magnetically stirred at 300 rpm for 1 hour until the mixture was completely melted to form a uniform transparent liquid, thereby obtaining choline chloride-oxalic acid dihydrate DES. The prepared DES was sealed and stored for future use; The enzyme-pretreated bamboo fiber (EBF) was dispersed in the prepared choline chloride-oxalate DES at a solid-liquid ratio of 10% (w / v), heated in an oil bath at 110°C, and magnetically stirred at 200 rpm for 4 hours to fully dissolve the lignin in the bamboo. After the treatment, the mixture was cooled to room temperature, deionized water was added as an anti-solvent, and vigorously stirred for 30 minutes to allow the lignin dissolved in the DES to precipitate and deposit on the surface of the bamboo fiber. The mixture was then repeatedly washed with deionized water until the washing liquid was neutral and colorless to remove residual DES and impurities. Finally, the mixture was dried in a 60°C forced air drying oven to constant weight to obtain bamboo fiber with in situ regenerated lignin on the surface (ERBF). Bamboo fiber (RBF) treated directly with DES was used as a control. Step 4. Preparation of bamboo fiber reinforced flexible polyurethane foam: polyether polyol, deionized water, silicone oil DC5043 and diethylaminoethanol (DEAE) were weighed according to the formula and mixed evenly in a beaker. ERBF was then added at 1, 2, 3, 4 and 5% of the total polyol mass and stirred at 3500 rpm for 1 min to uniformly disperse the bamboo fiber in the polyol system. MDI was then added and stirred vigorously at 3500 rpm for 10 s to fully mix the components. The mixture was quickly poured into a mold preheated to room temperature and foamed in a mold temperature controller. After foaming was completed, the foam was cured at room temperature for 24 h and then post-cured in a 60°C blast drying oven for 2 h to obtain polyurethane foam. The polyurethane foam without bamboo fiber was used as a blank control (BUF), and the polyurethane foams with in-situ regenerated lignin bamboo fiber (ERBF) added were marked as BPUF.
2. The method for preparing a bamboo fiber reinforced flexible polyurethane foam according to claim 1, wherein: The specifications of the choline chloride, oxalic acid, xylanase and ethanol used in the step 1 are all analytical grade; the specifications of the polyether polyol, isocyanate, diethylaminoethanol and silicone oil DC5043 used are all industrial grade.
3. The method for preparing a bamboo fiber reinforced flexible polyurethane foam according to claim 1, wherein: The pH of the phosphate buffer solution in step 2 is 5.
0.
4. The method for preparing a bamboo fiber reinforced flexible polyurethane foam according to claim 1, wherein: The thermogravimetric analyzer used in step 1 is TG 209F3; the constant temperature and humidity chamber is Testo 869; the mold temperature controller is REM-710; and the electronic balance is TPS2500S.
5. The method for preparing a bamboo fiber reinforced flexible polyurethane foam according to claim 1, wherein: The size of the mold in step 4 is 20 cm×20 cm×10 cm.
6. The method for preparing a bamboo fiber reinforced flexible polyurethane foam according to claim 1, wherein: In the step 3, the deionized water is added in a ratio of 1:10.